2007
DOI: 10.1142/s0219581x07005024
|View full text |Cite
|
Sign up to set email alerts
|

TOWARDS THE SINGLE-WALLED B- AND/OR N-DOPED CARBON NANOTUBES

Abstract: Soon after the discovery of carbon nanotubes (CNTs) in the early 1990's, the B-and/or N-doped CNTs began to attract increasing interest owing to their modified structural, physical and chemical properties. In comparison with the multi-walled nanotubes and nanofibers, substitutional doping of the single-walled nanotubes (SWNTs) has proved to be much more difficult, and it is only in very recent years that some experimental studies concerning the B-and/or N-doped SWNTs are emerging. This paper intends to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
0
3
1
Order By: Relevance
“…Chemical doping also can convert the metallic SWTN to semiconductor, which has been discussed by Zhi Xu [17] whose study showed that those boron/nitrogen co-doping metallic single wall carbon nanotubes will be converted to semiconductors. In contrast to the study of W. L. WANG et al [18], our results demonstrated substitutional P dopants within the nanotube C lattices is sp 3 coordinated rather than sp 2 coordinated. The constituting B, C and N elements are homogenously distributed within the SWNTs tube shells with no appreciable phase-separated B N and C domains, which have been synthesized by using the Bias-Assisted Hot filament chemical vapor deposition [19].…”
Section: Introductioncontrasting
confidence: 99%
“…Chemical doping also can convert the metallic SWTN to semiconductor, which has been discussed by Zhi Xu [17] whose study showed that those boron/nitrogen co-doping metallic single wall carbon nanotubes will be converted to semiconductors. In contrast to the study of W. L. WANG et al [18], our results demonstrated substitutional P dopants within the nanotube C lattices is sp 3 coordinated rather than sp 2 coordinated. The constituting B, C and N elements are homogenously distributed within the SWNTs tube shells with no appreciable phase-separated B N and C domains, which have been synthesized by using the Bias-Assisted Hot filament chemical vapor deposition [19].…”
Section: Introductioncontrasting
confidence: 99%
“…The discovery of carbon nanotubes (CNTs) has had a great impact on modern nanotechnology [1]. During the last decade, it has been revealed that the nitrogen-containing carbon nanotubes (NCNTs) possess outstanding physicochemical properties when compared with ordinary CNTs [2,3]. NCNTs were found to be important in the fabrication of new catalysts and fuel cells [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical doping has shown great success in silicon‐based semiconductors. This strongly implies that the electronic properties of SWCNTs should be tailored by appropriate doping during the synthesis process; just like that which has been used in Si‐based systems, nitrogen, boron, and phosphorous have been tried as dopants in SWCNTs 28–32. Since nitrogen and boron have similar atomic sizes to carbon, it is much easier for them to be inserted into the carbon structures.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, most reports have been about the doping of multiwalled carbon nanotubes (MWCNTs), possibly due to their higher structure tolerance 33. Bulk syntheses of doped SWCNTs have been performed by substitution reactions,34 arc discharge,35 laser ablation,36 and chemical vapor deposition (CVD) 28, 37. Xu et al proved that B/N co‐doping turns all SWCNTs to be semiconducting,29 while other reports have confirmed that carbon nanotubes behave metallically when doped by either B or N alone 30, 31.…”
Section: Introductionmentioning
confidence: 99%